The Impact of Industry-Adjusted Profitability and S-Curve Targeted Industry on Capital Structure: Evidence from Thailand - Sirada Nuanpradit (Asian Academy of Management Journal of Accounting and Finance, 2023)
This study examines the impact of industry-adjusted profitability and S-curve targeted industries under an innovation-driven economy on firms’ capital structures in Thailand. The results demonstrate that a superior degree of industry-adjusted profitability reduces the need for debt financing. Within the industry, franchise and harvest firms with sufficient earnings have a lower debt overhang than under-performing firms. Furthermore, the S-curve targeted industries, which typically use debt to finance their expensive investments, appear to use fewer loans when they feel pressured by the investment support policy to intensify research and development (R&D) activities. Overall, in the emerging market geared toward a new economic roadmap, firms’ capital structures are shaped by competitive performance as well as industry and policy forces.